Integration of DeLone and McLean and self-determination theory in internet banking continuance intention context. Issue 3 (5th August 2019) - Rahi, Samar; Abd.Ghani, Mazuri
Abstract : Purpose: The proliferation of information technology has changed the banking system globally. Internet technology has not only allowed banks to offer products and services but also improved their ability to retain customers. This study aims to examine internet banking user's continuance intention by integrating two well-known theories DeLone and McLean information system success model (D&M) and self-determination theory (SDT). Design/methodology/approach: The research model was tested using survey data from 398 customers of commercial banks. The respondents were internet banking users. Data were analyzed using structural equation modeling. Findings: The results revealed that internet banking user continuance intention is jointly determined by information quality (INFQ), service quality, satisfaction, introjected regulation, external regulation, intrinsic regulation and identified regulation. The integrated model explained 75.4 per cent variation in customer's continuance intention to use internet banking. The results suggested that intrinsic regulation and identified regulation were the most important human motivation factors that drive customer's intention toward continue use of internet banking. Practical implications: The findings imply that managers seeking user satisfaction should focus on INFQ and service quality to enhance user continuance intention. Policymakers should focus on intrinsic and identified regulation of internet banking users. Some of the ways banks can do this is to develop enjoyable internet banking website with kind of reward system, activities that have the charm of novelty, challenge or aesthetic significance will help to improve user's intention to continue use of internet banking. Originality/value: This study contributes to the literature by integrating D&M and SDT in continuance intention and different from several traditional studies that had investigated the initial acceptance of internet banking users.